COMPLIANCE TO BLOOD SUPPLEMENT TABLETS CONSUMPTION AMONG TEENAGERS HIGH SCHOOL AS AN EFFORT TO PREVENT ANEMIA IN INDONESIA - Anggraini, Nofa; Lisnawati, Luthfiyah; Juita, Desma; Hariyanti, Ending Tri (DPW PPNI Provinsi Jawa Barat, 2024)
Aims : Anemia, a global micronutrient issue, affects 30% of the population, particularly in developing countries. Southeast Asia has a high prevalence of anemia, with women of reproductive age experiencing it at 46.6% in 2019. The Indonesian government has implemented a Blood Supplement Tablet program for teenagers, but coverage remains low at 31.1% in 2021. Objective : to know the factors that affect compliance in teenagers as an effort to prevent anemia. Method : This is a quantitative analytic study with a cross-sectional approach, which population was female students from three schools located in three different provinces in Indonesia. The sample size was calculated using the G-Power Software application, the total sample was found to be 134 which was sorted into three groups with the same proportion. So that each research location got a total sample of 44.67 which was rounded up to 45 samples. Result : From this research, it was found that there was a relationship between attitudes and the support of their friends with the level of consumption of Blood Supplement Tablets in teenagers (p value 0.000) in MAN 4 Karawang (West Java), SMA BPS&K 1 Jakarta (DKI Jakarta), and SMAN 1 Siberut Barat Daya (West Sumatra ) . Then, there is a relationship between knowledge and the level of compliance with consumption of Blood Supplement Tablets in teenagers (p value 0.000) in SMA BPS&K 1 Jakarta (DKI Jakarta) and SMAN 1 Siberut Barat Daya (West Sumatra). Meanwhile, in MAN 4 Karawang (West Java), there was no relationship between knowledge and the level of compliance of Blood Supplement Tablets consumption among teenagers (p value 0.191). Conclusion : There was also an association between parental support and the level of compliance of Blood Supplement Tablets consumption among teenagers (p value 0.000) in MAN 4 Karawang (West Java) and SMA BPS&K 1 Jakarta (DKI Jakarta).